Before Belief: Embodiment and the “Trying Game” - Donna Strickland (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
I use my experience of teaching "Mindful Writing" to reflect on the pre-cognitive act of "trying out" new ideas. It seems that there's an important piece of the believing game that happens before the cognitive act of belief and that involves the body as much as the mind.